Hammer blows to the head. (August 2019) - Ramsthaler, F.; Kettner, M.; Potente, S.; Verhoff, M.A.; Seibert, H.; Reis, M.; Diebels, S.; Roland, M.
Abstract: Hammer blows cause serious, often fatal injuries, especially when massive blunt violence is targeted at the head region. The evaluation of the injury potential depends not only on the body region hit, but also on the characteristics of the hammer as a weapon and on the physical characteristics of the attacker. This study aimed at elucidating the dependency between the physical constitution of a perpetrator and the intensity of hammer blows, thus to verify or refute this seemingly obvious interrelation sometimes expressed in the saying that a "strong hand strikes harder". For this purpose, 113 volunteers of different ages and sexes took part in different experimental settings. While, as expected, clear differences between male and female were detectable in the striking power of single and multiple strokes, there were no age or sex differences with regard to the maximum number of strokes per time unit. Strength differences in slamming with a hammer between men and women exceeded expectations in this study. Using the fracture forces as described by Sharkey et al. in an exemplary manner, one can expect a fracture of the skull in 9 out of 10 cases with a 300 g hammer by men for intensively executed single strokes, whereas this was only the case for approx. 2/10 women in this study. The maximum circumference of the upper arm and the width of the shoulder girdle correlate significantly with the achievable impact forces of individual hammer blows in both sexes. A simple measurement of the hand force with a manometer using the regression formula y [kN] = 0.144 × manual grip force −1.08 can be used as a rough estimation parameter for the theoretically achievable impact force. If one strikes repeatedly with the same hammer for 1 min, the magnitude of a single strike decreases continuously from 4.5 kN to 2.6 kN on average. If a 1500 g hammer is used instead of a 300 g hammer, one does not get the fivefold impact force you might expect at first sight, but only on the order of twice the impact force, about 14 kN on average. The results prove the importance of physical experiments, whose results can help to better interpret the magnitude and effects of hammer blows as a form of potentially life-threatening violence.